The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/aos.12529
|View full text |Cite
|
Sign up to set email alerts
|

The use of endoscopic cyclophotocoagulation for moderate to advanced glaucoma

Abstract: ABSTRACT.Endoscopic Cyclophotocoagulation (ECP) is a glaucoma surgery designed to reduce the intraocular pressure (IOP) by partially ablating the ciliary processes to decrease aqueous humour production and secretion. The aim of this paper is to review the literature regarding the background, indications and results of the surgery. Although there are case reports of visually devastating complications, including persistent hypotony and phthisis, the use of ECP is often reported in eyes with advanced diseases. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…With respect to transscleral cyclophotocoagulation, which is reserved to intractable and advanced glaucoma, the endoscopic cyclophotocoagulation (ECP) is used also in nonrefractory cases, without absolute contraindications [7173]. ECP has numerous advantages over transscleral cyclophotocoagulation, since the target tissue is directly visualized and, therefore, overtreatment is usually avoided.…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to transscleral cyclophotocoagulation, which is reserved to intractable and advanced glaucoma, the endoscopic cyclophotocoagulation (ECP) is used also in nonrefractory cases, without absolute contraindications [7173]. ECP has numerous advantages over transscleral cyclophotocoagulation, since the target tissue is directly visualized and, therefore, overtreatment is usually avoided.…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
“…In POAG, the IOP reduction was found to range from 18% to 47% (3.9 to 10.9 mmHg), with a mean IOP decrease of 31% (7 mmHg). In advanced secondary glaucoma, the IOP reduction ranged from 26% to 68% (7 to 28 mmHg) or yielded a mean IOP decrease of 50% (18 mmHg) [70, 71, 7476]. In the largest retrospective study on ECP (7.4 years of follow-up), Lima et al reported a postoperative IOP ranging between 6 and 21 mmHg in 79% of patients, with a mean number of medications of 1.9 [75].…”
Section: Cyclodestructive Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the population and forms of glaucoma treated, published studies usually report a comparable or slightly lower ability to reduce IOP. However, it should be mentioned that it might be hard to draw a comparison from previous studies, as the criteria for success are frequently different and, as the patients treated are in some of the studies performed with the diode laser cyclophotocoagulation, most have secondary and refractory glaucoma (Kaplowitz et al 2014). Similarly, systematic review or meta-analysis has described the ability of the filtering surgeries -particularly the trabeculectomy -to decrease IOP (Eldaly et al 2014;Zhou et al 2014).…”
Section: Retreatmentmentioning
confidence: 99%
“…Trabeculectomy and deep sclerectomy [6–8] have been used most commonly. Additionally, cyclophotocoagulation [9,10] provides an alternative therapy to lower IOP by decreasing the aqueous humor production.…”
Section: Introductionmentioning
confidence: 99%